2020
DOI: 10.1111/jbi.14005
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐related geographical variation in performance traits across the invasion front of a widespread non‐native insect

Abstract: Aim Invasive species are ideal systems for testing geographical differences in performance traits and measuring evolutionary responses as a species spreads across divergent climates and habitats. The European gypsy moth, Lymantria dispar dispar L. (Lepidoptera: Erebidae), is a generalist forest defoliator introduced to Medford, Massachusetts, USA in 1869. The invasion front extends from Minnesota to North Carolina and the ability of this species to adapt to local climate may contribute to its continuing spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 70 publications
5
26
2
Order By: Relevance
“…We found evidence that source populations responded differently to experimental treatments (Figure 2c). However, evidence for local adaptation of larval growth and development was equivocal overall, in contrast to other recent studies (Faske et al, 2019; Friedline et al, 2019; Thompson et al, 2017, 2021). Among-population variation in larval growth rates in the baseline and CC4.5 treatments was not discernibly related to a “home field advantage” as was seen in the CC8.5 treatments.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…We found evidence that source populations responded differently to experimental treatments (Figure 2c). However, evidence for local adaptation of larval growth and development was equivocal overall, in contrast to other recent studies (Faske et al, 2019; Friedline et al, 2019; Thompson et al, 2017, 2021). Among-population variation in larval growth rates in the baseline and CC4.5 treatments was not discernibly related to a “home field advantage” as was seen in the CC8.5 treatments.…”
Section: Discussioncontrasting
confidence: 80%
“…We focus here on data from third and fifth instars because fungal contamination of the artificial diet increased mortality between fifth instar and adulthood in individuals raised in one of the laboratories (Figure S2). Data from this and a previous experiment (Thompson et al, 2021) showed that larval masses were strongly correlated with pupal masses (Table S1), which in turn, are an excellent proxy for fecundity (Faske et al, 2019; Honěk, 1993).…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…In addition, climatic factors in some regions may permit more rapid population growth (and increased agricultural impacts) due to multiple generations of any given successfully-established haplotype (Musolin et al 2019;Stoeckli et al 2020). However, variation in performance traits in invasive insect species can be an important predictor of their success in establishment and spread across a broad geographic range (Thompson et al 2021). Future research investigating the different H. halys haplotypes would be of interest to determine whether there is any validity to the observation that H1 appears to be a more successful invader and to determine whether this success is linked to intraspecific variation in biological traits, such as phenology, thermal performance, flight capacity, overwintering survival or fecundity.…”
Section: Discussionmentioning
confidence: 99%